2015
DOI: 10.1159/000440642
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the Oxygenation Response to Inspired Oxygen Adjustments in Preterm Infants

Abstract: Background: Oxygen saturation (SpO2) targeting in the preterm infant may be improved with a better understanding of the SpO2 responses to changes in inspired oxygen (FiO2). Objective: We investigated the first-order FiO2-SpO2 relationship, aiming to quantify the parameters governing that relationship, the influences on these parameters and their variability. Methods: In recordings of FiO2 and SpO2 from preterm infants on continuous po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
(34 reference statements)
1
10
0
Order By: Relevance
“…Our initial concern that fast FiO 2 responses to SpO 2 changes result in more episodes of hypoxaemia and/or hyperoxaemia was not confirmed in our study. Sadeghi Fathabadi et al 16 found a median delay in first order responses in SpO 2 following FiO 2 increments or decrements of 22 s and 40 s, respectively, which virtually fits our present waiting time of 30 s. However, some SpO 2 responses to an FiO 2 change occur after this wait time, which may increase the risk of hypoxaemia or hyperoxaemia. In our study, Target% was distinctly higher during CLAC slow compared with CLAC fast in five patients (see online supplementary figure 2S).…”
Section: Discussionsupporting
confidence: 84%
“…Our initial concern that fast FiO 2 responses to SpO 2 changes result in more episodes of hypoxaemia and/or hyperoxaemia was not confirmed in our study. Sadeghi Fathabadi et al 16 found a median delay in first order responses in SpO 2 following FiO 2 increments or decrements of 22 s and 40 s, respectively, which virtually fits our present waiting time of 30 s. However, some SpO 2 responses to an FiO 2 change occur after this wait time, which may increase the risk of hypoxaemia or hyperoxaemia. In our study, Target% was distinctly higher during CLAC slow compared with CLAC fast in five patients (see online supplementary figure 2S).…”
Section: Discussionsupporting
confidence: 84%
“…The time delay we measured can be compared with patient data published by Fathabadi et al [12] and in Krone's master thesis [11]. The time delay presented in Table 1 and demonstrated in Figure 4 shows irregularities in the decreasing trend.…”
Section: Discussionmentioning
confidence: 72%
“…Original research significant time delay between FiO 2 adjustment and when SpO 2 reaches a new stable level. 11 Given both the importance and difficulty of SpO 2 targeting, automated oxygen control (AOC) is a logical improvement on current practice. In essence, the concept is of an SpO 2 input to a device holding a set of computational instructions (an algorithm), which then gives an output, an updated value for FiO 2 .…”
Section: What This Study Adds?mentioning
confidence: 99%